Enhanced blood-brain barrier penetration and glioma therapy mediated by T7 peptide-modified low-density lipoprotein particles - Meng Liang; Chunhong Gao; Yuli Wang; Wei Gong; Shiyao Fu; Lin Cui; Zhenhan Zhou; Xiaoyang Chu; Yue Zhang; Qianqian Liu; Xiong Zhao; Baoquan Zhao; et al. (Taylor & Francis Group, 2018)
Therapeutic outcome for the treatment of glioma was often limited due to the non-targeted nature and low permeability of drugs across the blood-brain barrier (BBB). An ideal glioma-targeted delivery system need to traverse the BBB and then target glioma cells with adequate optimized physiochemical properties and biocompatibility. However, it is an enormous challenge to the researchers to engineer the above-mentioned features into a single nanocarrier particle. New frontiers in nanomedicine are advancing the research of new biomaterials. In this study, we demonstrate a strategy for glioma targeting by encapsulating vincristine sulfate (VCR) into a naturally available low-density lipoprotein particles (LDL)-based drug delivery system with the modification of T7 peptide ligand (T7-LDL). LDL, endogenous lipid transporters, can specifically bind to brain endothelial cells and glioma cells via interacting with the low-density lipoprotein receptors (LDLR). T7 is a seven-peptide ligand of transferrin receptors (TfR) capable of circumventing the BBB and then targeting glioma. By combining the dual-targeting delivery effect of T7 peptide and parent LDL, T7-LDL displayed higher glioma localization than that of parent LDL. After loading with VCR, T7-LDL showed the most favorable antiglioma effect in vitro and in vivo. These results demonstrated that T7-LDL is an important potential drug delivery system for glioma-targeted therapy.